If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (X + -3)(3 + -1y) = 0 Reorder the terms: (-3 + X)(3 + -1y) = 0 Multiply (-3 + X) * (3 + -1y) (-3(3 + -1y) + X(3 + -1y)) = 0 ((3 * -3 + -1y * -3) + X(3 + -1y)) = 0 ((-9 + 3y) + X(3 + -1y)) = 0 (-9 + 3y + (3 * X + -1y * X)) = 0 (-9 + 3y + (3X + -1yX)) = 0 Reorder the terms: (-9 + 3X + 3y + -1yX) = 0 (-9 + 3X + 3y + -1yX) = 0 Solving -9 + 3X + 3y + -1yX = 0 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '9' to each side of the equation. -9 + 3X + 3y + 9 + -1yX = 0 + 9 Reorder the terms: -9 + 9 + 3X + 3y + -1yX = 0 + 9 Combine like terms: -9 + 9 = 0 0 + 3X + 3y + -1yX = 0 + 9 3X + 3y + -1yX = 0 + 9 Combine like terms: 0 + 9 = 9 3X + 3y + -1yX = 9 Add '-3y' to each side of the equation. 3X + 3y + -3y + -1yX = 9 + -3y Combine like terms: 3y + -3y = 0 3X + 0 + -1yX = 9 + -3y 3X + -1yX = 9 + -3y Reorder the terms: -9 + 3X + 3y + -1yX = 9 + -3y + -9 + 3y Reorder the terms: -9 + 3X + 3y + -1yX = 9 + -9 + -3y + 3y Combine like terms: 9 + -9 = 0 -9 + 3X + 3y + -1yX = 0 + -3y + 3y -9 + 3X + 3y + -1yX = -3y + 3y Combine like terms: -3y + 3y = 0 -9 + 3X + 3y + -1yX = 0 The solution to this equation could not be determined.
| .5x+.375x+x= | | 24*2x*x=72000 | | -2n-2=-2n-7 | | 12k=8 | | 3.4(x+3)=15.3 | | 12(x)=5(y) | | z^2-(1+2i)z+1+7i=0 | | 6(4-x)+6x=244 | | 299,792,000/x=0.50 | | 0.5x+2x=7 | | 7-6x=x-49 | | .5(3x-24)=9 | | 6x-(2x+7)=3+4(x-9) | | 2x+1=3+4x | | m^2+16m=-49 | | -8m-10+6m=36 | | 5x^2+18x+45=0 | | 5x+9=15-6 | | 1+8y=-32 | | X^2-4x-12y+16=0 | | 8+6x+3x=-10 | | 3k-15=78 | | 8(5n-4)+8=-264 | | 6c-64=80 | | Y/3-15=-6 | | -7m-5=37 | | 4m+70=-30 | | 8y+4(7+y)=3(y-2)+10 | | p(t)=(348)3t/4 | | 4+7x-5x=-6 | | W=2x+2y | | 11(x)=4(y) |